Microscopic reconstruction and immunohistochemical analysis of discomalleolar ligament. Issue 8 (August 2020) - Anastasi, Michele Runci; Rizzo, Giuseppina; Nicita, Fabiana; Bramanti, Alessia; Milardi, Demetrio; Macchi, Veronica; Brunetto, Dario; Cascone, Piero; Arco, Alba; Nicita, Arianna; Anastasi, Giuseppe; Favaloro, Angelo
Abstract: Discomalleolar ligament represents the vestiges of the primitive lateral pterygoid muscle which penetrates in the caudal end of Meckel's cartilage; during the development of newborn, the petrotympanic fissure close almost completely leaving inside the discomalleolar ligament. After entering in tympanic cavity, some fibers of the discomalleolar ligament insert to walls of cavity, other fibers continue with the lateral margin of the anterior ligament and insert in the neck of malleus; in contrast, other Authors demonstrated that discomalleolar ligament is an independent structure inserted in proximity of the neck of the malleus. Although the discomalleolar ligament can be considered as a structure of clinical importance, it is not described by anatomy textbooks. Moreover, it is likely that important correlations between temporomandibular diseases and otological symptoms exist. We have studied discomalleolar ligament submitting the specimens to the 3D volume rendering technique, light microscopy, reconstructing a wide light microscopic fields to analyze the real connection between retrodiscal connective tissue and middle ear, and immunofluorescence methods in order to analyze the consistence of ligament. We have shown two types of connections between TMJ and ear: first, with external acoustic meatus and, second, with middle ear through discomalleolar ligament. The different insertion represents a strong support in order to demonstrate that the TMJ disorders can determine variations of tension that are transmitted on the tympanic membrane provoking tinnitus in according to clinical features. Then, we propose that it is necessary to mention, also in anatomy textbook, the discomalleolar ligament as ligament distance of TMJ. Abstract : Biological sciences; Cell biology; Health sciences; Anatomy; Medical imaging; Discomalleolar ligament; Petrotympanic fissure; Tympanic membrane; Temporomandibular joint; Tinnitus